Predicting mortality dynamics in cancer patients: A machine learning approach to pre-death events - Tatsuki Yamamoto; Minoru Sakuragi; Yuzuha Tuji; Yuji Okamoto; Eiichiro Uchino; Motoko Yanagita; Manabu Muto; Mayumi Kamada; Yasushi Okuno (PLoS ONE, 2025)
Capturing the dynamic changes in patients’ internal states as they approach death due to fatal diseases remains a major challenge in understanding individual pathologies and improving end-of-life care. However, existing methods primarily focus on specific test values or organ dysfunction markers, failing to provide a comprehensive view of the evolving internal state preceding death. To address this, we analyzed electronic health record (EHR) data from a single institution, including 8,976 cancer patients and 77 laboratory parameters, by constructing continuous mortality prediction models based on gradient-boosting decision trees and leveraging them for temporal analyses. We applied Shapley Additive exPlanations (SHAP) to assess the contribution of individual features over time and employed a SHAP-based clustering approach to classify patients into distinct subtypes based on mortality-related feature dynamics. Our analysis identified three distinct clinical patterns in patients near death, with key laboratory parameters—including albumin, C-reactive protein, blood urea nitrogen, and lactate dehydrogenase—playing a critical role. Dimensionality reduction techniques demonstrated that SHAP-based patient stratification effectively captured hidden variations in terminal disease progression, whereas traditional stratification using raw laboratory values failed to do so. These findings suggest that machine learning-driven temporal analysis can reveal clinically meaningful state transitions that conventional approaches overlook, offering new insights into the heterogeneous nature of terminal disease progression. This framework has the potential to enhance personalized risk stratification and optimize individualized end-of-life care strategies by identifying distinct patient trajectories that may inform more targeted interventions.